Core–Shell–Shell and Hollow Double‐Shell Microgels with Advanced Temperature Responsiveness. Issue 2 (29th October 2014) - Dubbert, Janine; Nothdurft, Katja; Karg, Matthias; Richtering, Walter; Frey, H.; Mecking, S.
<x xml:space="preserve">Abstract</x> Unique doubly temperature‐responsive hollow microgels are presented. These consist of two concentric thermoresponsive polymer shells made of poly(N‐isopropylacrylamide) (PNIPAM) and poly(N‐isopropylmethacrylamide) (PNIPMAM), respectively. The hollow particles are derived from silica‐PNIPAM‐PNIPMAM core‐shell–shell (CSS) particles by dissolution of the silica core. Light scattering measurements reveal the twofold volume phase transition behavior that occur in the PNIPAM and PNIPMAM regions of the CSS and the respective hollow particles. In the presence of the silica core, i.e., in case of the CSS particles, the swelling of the inner shell is tremendously restricted by the core. However, after the core is dissolved, the transition of the inner shell from the swollen to the collapsed state is highly pronounced. This versatile approach allows preparing hollow particles with individually tunable properties on the particle inside and outside for various applications as multifunctional smart materials. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>